"A Golly was simply a toy. End of": Inoculation, attention deflection, and attempted puzzle‐resolution in contesting racism in online discussions. (12th December 2019) - McVittie, Chris; McKinlay, Andy; Munro, Rachel
Abstract: In producing arguments against minority groups that are designed to avoid accusations of prejudice, speakers routinely deploy two discursive strategies. One strategy of "inoculation" seeks to ward off such accusations, while the other strategy of "attention deflection" directs attention away from the potential target group. Where despite use of one or both strategies accusations arise, the result is a puzzle that needs to be resolved through explanation. Here, in a discourse analysis of online discussions as to whether "blacking up" is to count as racism, we see contributors contest (a) whether absence of intention to offend inoculates individuals from accountability for potentially racist actions, (b) whether "blacking up" depicts toys/characters rather than people, and (c) whether attempted explanations of accusations of racism work to resolve the apparent puzzle that has arisen. Contributors do not reach any consensus. These findings point to the difficulties in attempting to challenge potential racism.